2022
DOI: 10.3390/polym14245455
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Aqueous Dispersing of Carbon Black Nanoparticles Surface-Coated with Styrene Maleic Acid (SMA) Copolymer

Abstract: Carbon black (CB) particles tend to aggregate in aqueous solutions, and finding an optimum dispersing condition (e.g., selection of the type of dispersant) is one of the important tasks in related industries. In the present study, three types of styrene maleic acid (SMA) copolymer dispersants were synthesized, labeled respectively ‘SMA-1000’, ‘SMA-2000’, and ‘SMA-3000’, which have 1, 2, and 3 styrene groups in their repeating units. Then, asymmetrical flow field-flow fractionation (AsFlFFF) was employed to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The dispersion of CB in the aqueous solution is determined by the interaction between particles, solvent, and dispersant. Between the particle and the aqueous solution, interfacial tension and adsorption are influential, while between the particle and the dispersant, affinity plays a role [44] . SHMP is a typical low molecular weight (LMW) compound, which cannot provide sufficient steric hindrance to organic particles with atoms such as carbon compared to high molecular weight ones (HMW).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersion of CB in the aqueous solution is determined by the interaction between particles, solvent, and dispersant. Between the particle and the aqueous solution, interfacial tension and adsorption are influential, while between the particle and the dispersant, affinity plays a role [44] . SHMP is a typical low molecular weight (LMW) compound, which cannot provide sufficient steric hindrance to organic particles with atoms such as carbon compared to high molecular weight ones (HMW).…”
Section: Resultsmentioning
confidence: 99%
“…Between the particle and the aqueous solution, interfacial tension and adsorption are influential, while between the particle and the dispersant, affinity plays a role. [44] SHMP is a typical low molecular weight (LMW) compound, which cannot provide sufficient steric hindrance to organic particles with atoms such as carbon compared to high molecular weight ones (HMW). However, several studies have shown that phosphate ions bond more strongly to TiO 2 by inner-sphere surface complexation.…”
Section: Binary Particle Systemmentioning
confidence: 99%
“…In this study, our objective is to develop a highly efficient CMP slurry. This slurry will incorporate calcined ceria nanoparticles along with an SMA dispersant polymer, with the addition of three types of defoaming polymers (PPG) using various concentrations based on the SMA dispersant in the previous work [ 39 ]. The goal is to overcome particle agglomeration, stable polishing uniformity, and scratches among particles.…”
Section: Introductionmentioning
confidence: 99%
“…It has a high surface area-to-volume ratio and is widely used in a plethora of applications due to its excellent resistance to chemicals, light, and temperature . Some of the common uses of CB are in rubber products, coatings and paints, plastics, and batteries. A recent review by Andrioli et al highlights the current scientific importance of CB in renewable energy harvesting and environmental remediation. CB and functionalized CB materials have been proven to be essential and competitive against other carbon nanomaterials for supercapacitors, CO 2 separations, and batteries and as catalyst support in solar and fuel cells. In addition, CB is the largest industrially produced nanocarbon with a projected annual manufacture of 15 Mt by 2025 …”
Section: Introductionmentioning
confidence: 99%